New approaches for the synthesis of advanced precursors of Rhazinilam analogues - Kholod Zaitseva, Inga (My University, 2014)
The purpose of this thesis was to explore different approaches for the synthesis of advanced precursors of rhazinilam analogues. The intramolecular Michael Addition was envisaged in order to obtain the pyrrole or pyrrolinone based analogues. The aim of the first project was to develop a flexible, efficient synthesis towards model systems. N-acylation and N-alkylation of the corresponding substrates were intensively studied.
Oxydizing the pyrrole ring to pyrrolinone and blocking the C-5 position on the pyrrolinone ring seem to be a promising way to increase the chemical stability of rhazinilam analogues and avoid its enzymatic deactivation in target cells. The second project focused on the preparation of highly substituted 2-pyrrolidinones by a key Mukaiyama aldol reaction – Staudinger type reductive cyclisation sequence.
Thèse de doctorat : Université de Neuchâtel, 2014
Keywords: Rhazinilam; Rhazinilam analogues; Crossed Aldol Mukaiyama reaction; Staudinger type reductive cyclisation; Diastereoselectivity; 3-pyrrolin-2-ones; N-acylation; N-alkylation